A photosensitive sustainable lignin nanoplatform for multimodal image-guided mitochondria-targeted photodynamic and photothermal therapy. (December 2022) - Liu, X.; Li, M.; Li, X.; Ge, M.; Liu, S.; Li, S.; Li, J.; Ding, J.; Ragauskas, A.J.; Sun, W.; James, T.D.; Chen, Z.
Abstract: Photoactivated nanocarriers exhibit significant potential for anticancer therapy, but complex design strategies, unsustainable substrates, and short wavelengths limit their practical application. Here, we designed a new lignin-derived photoactivated nanomaterial that exploits the sensitivity of the β - O -4 bond of lignin to singlet oxygen. This sustainable product was loaded with mitochondria-targeting chlorin e6 and black phosphorus quantum dots (BPQDs) to produce BPQDs@N-LgC NPs, which were used for mitochondria-targeted fluorescence/photoacoustic-guided photothermal and photodynamic therapy. When irradiated at 808 nm, the BPQDs in BPQDs@N-LgC NPs exhibited good photothermal conversion, which allowed photoacoustic imaging and inhibited tumor growth. When irradiated at 660 nm, the BPQDs@N-LgC NPs generated fluorescence and reactive oxygen species, which allowed photoluminescence imaging and further inhibited tumor growth. Cleavage of the β - O -4 bond of lignin by photo-triggered reactive oxygen species degraded the NPs and released the BPQDs, facilitating rapid excretion of the therapeutic nanomaterials. Our rationally designed BPQDs@N-LgC NPs exhibited good therapeutic efficacy, both in vitro and in vivo . Graphical abstract: Image 1 Highlights: N-LgC was established as a light-sensitive lignin platform for phototherapy. N-LgC capable of mitochondria-targeting multi-modal imaging. N-LgC facilitates multifunctional photodynamic and photothermal therapy.